Immunotoxicity from checkpoint inhibitor therapy: clinical features and underlying mechanisms. - Fessas,P; Possamai,LA; Clark,J; Daniels,E; Gudd,C; Mullish,BH; Alexander,JL; Pinato,DJ (Immunology, 2020)
Immune checkpoint inhibition with monoclonal antibodies is becoming increasingly commonplace in cancer medicine, having contributed to a widening of therapeutic options across oncological indications. Disruption of immune tolerance is the key mechanism of action of checkpoint inhibitors and although immune-related adverse events are a typical class effect of these compounds, the relationship between toxicity and response is not fully understood. Awareness and vigilance are paramount in recognizing potentially life-threatening toxicities and managing them in a timely manner. In this review article, we provide an overview of the clinical features, pathological findings and management principles of common immune-related toxicities, attempting to provide mechanistic insight into an increasingly common complication of cancer therapy.